2014
DOI: 10.1089/hum.2014.030
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing Public Perceptions of the Ethics of Gene Therapy

Abstract: Gene therapy research is advancing rapidly, and hopes of treating a large number of brain disorders exist alongside ethical concerns. Most surveys of public attitudes toward these ethical issues are already dated and the content of these surveys has been researcher-driven. To examine current public perceptions, we developed an online instrument that is responsive and relevant to the latest research about ethics, gene therapy, and the brain. The 16-question survey was launched with the platform Amazon Mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 23 publications
2
62
1
1
Order By: Relevance
“…As noted earlier, attitudes toward gene editing reflected two broadly distinct-albeit moderately correlatedlatent factors concerning treatment and enhancement. This finding had been hinted at in recent work (Gaskell et al, 2017;Robillard et al, 2014;Xiang et al, 2015), but prior to the current study had not been formally established. As such, these results indicate that future research into gene editing attitudes should consider using distinct scales with regard to these issues as well as seeking to further understand and establish the latent architecture of attitudes in this domain.…”
Section: Discussionmentioning
confidence: 53%
“…As noted earlier, attitudes toward gene editing reflected two broadly distinct-albeit moderately correlatedlatent factors concerning treatment and enhancement. This finding had been hinted at in recent work (Gaskell et al, 2017;Robillard et al, 2014;Xiang et al, 2015), but prior to the current study had not been formally established. As such, these results indicate that future research into gene editing attitudes should consider using distinct scales with regard to these issues as well as seeking to further understand and establish the latent architecture of attitudes in this domain.…”
Section: Discussionmentioning
confidence: 53%
“…These findings are consistent with public opinion polls. 30,[32][33][34][35][36][37][38][39][40][41] Moving forward, there will be a need to define more precisely what conditions constitute a ''therapeutic application''; this is an important area of future study.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined public attitudes toward human gene editing in the United States, Canada, the United Kingdom, Japan, and China. [30][31][32][33][34][35][36][37][38][39][40][41] A metaanalysis of U.S. public opinion polls 30 found that most Americans favor somatic editing for clinical use in patients with serious diseases, with fewer supporting germline editing.…”
Section: Introductionmentioning
confidence: 99%
“…As both studies took place through online platforms, it is important to acknowledge the limitations of our samples: while both Yahoo! Answers and Amazon's Mechanical Turk boast high Adapted from [10], with permission.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent online survey explored the ethics themes expressed on Yahoo! Answers in greater depth [10]. Results from these studies are discussed in this article.…”
mentioning
confidence: 97%